Romanism in Latin American Jurists - González de Cancino, Emilssen (1986)
This article explores the influence of Roman law on Latin American law, highlighting how it has molded both the civil law codification and the legal education. Romanism is presented as a central element in the teaching of law and the interpretation of codes in Latin America. The article also presents the impact of Roman sources on judicial practice, highlighting their use to sustain arguments, broaden the interpretation of laws, and address complex legal problems. In this framework, special attention is given to the work of Ricardo Hinestrosa Daza, whose judicial decisions show a great knowledge of Roman law, using aphorisms, technical concepts in Latin and implicit references to Roman sources. After an exhaustive study of his sentences, it becomes evident the survival of Roman law in Colombian jurisprudence and the importance of its legacy in legal education. Finally, the author invites to continue with the research on the validity and value of Roman law in the development of modern Latin American law.